CD28 Signaling Drives Notch Ligand Expression on CD4 T Cells - Mitra, Ankita; Shanthalingam, Sudarvili; Sherman, Heather L.; Singh, Khushboo; Canakci, Mine; Torres, Joe A.; Lawlor, Rebecca; Ran, Yong; Golde, Todd E.; Miele, Lucio; Thayumanavan, Sankaran; Minter, Lisa M.; et al. (Frontiers in Immunology, 2020)
Notch signaling provides an important cue in mammalian developmental. It is a key player in T cell development and function. Notch ligands, such as Delta-like ligands (DLL) 1, 3, 4 and Jagged 1, 2, can impact Notch signaling positively or negatively, by trans-activation or cis-inhibition. Trans and cis interactions are receptor-ligand interaction on two adjacent cells and interaction on the same cell respectively. The former sends an activation signal and the latter, a signal for inhibition of Notch. However, earlier reports suggested that Notch is activated in the absence of Notch ligand-expressing APCs in a purified population of CD4 T cells. Thus the role of ligands in Notch activation, in a purified population of CD4 T cells, remains obscure. In this study we demonstrate that mature CD4 T cells are capable of expressing Notch ligands on their surface very early upon activation with soluble antibodies against CD3 and CD28. Moreover, signaling solely through CD28 induces Notch ligand expression and CD3 signaling inhibits ligand expression, in contrast to Notch which is induced by CD3 signaling. Additionally, by using decoys mimicking the Notch extracellular domain, we demonstrated that DLL1, DLL4, and JAG1, expressed on the T cells, can cis-interact with the Notch receptor and inhibit activation of Notch. Thus, our data indicate a novel mechanism of the regulation of Notch ligand expression on CD4 T cells and its impact on activated Notch.